The Development of Small Lodging Business Networking for Sustainability Crisis Management in Pranburi District, Prachuap Khiri Khan Province - Aiamssard, Chissanu; Taweephol, Rachanon (RMUTI Journal Humanities and Social Sciences, 2024)
The objectives of this research were 1) To analyze the context and situation of entrepreneur small lodging business and 2) The development of small lodging business networking for sustainability crisis management. It was qualitative research with a phenomenology methodology, data were collected by in-depth interviews from the key informants with small lodging entrepreneurs in the area of Pranburi districts with 17 peoples. Then data were collected by focus group discussion methodology with representatives of small lodging business operators, government, lecturer in the Hospitality and Tourism Industry, tourist, and other service business operators totaling 25 people. The results of the study revealed that 1) The context and operating conditions of small lodging business operators are as follows: 1.1) Reducing the burden of operating expenses, The addition of monthly room service, Participating in the governments We Travel Together project, Increasing reservation channels and public relations via social media and 1.2) Restrictions related to the number of employees and the number of rooms is insufficient to support during the tourist season. Including the resurgence of the COVID-19 and 2.1) The development of a network of small lodging entrepreneurs must determine a horizontal network format. Determining objectives to build relationships and promote tourism potential establishing relationship-building activities between members are formal and informal, and determining network coordinators via social media contact. 2.2) Sustainable Crisis Management, consisting of 2.2.1) Before crisis; a plan to prepare for dealing with crises. 2.2.2) During crisis; a communication plan to reduce the impact caused by misunderstanding and panic among stakeholders and 2.2.3) After crisis; a plan for rehabilitation to build confidence in the organization’s image.